Proteomic analysis and pharmacological activities of the venom of the Moroccan cobra Naja haje legionis - Malih, Ibitissam; Ahmad Rusmili, Muhamad Rusdi; Ting, Yee Tee; Saile, Rachid; Ghalim, Noreddine; Othman, Iekhsan (Elsevier, 2012)
Background: In Morocco, envenomation by snake bites poses a serious problem to public health. The cobra Naja haje legionis is endemic of the country and one of the most dangerous species known. In this work, we report the proteomic and pharmacological characterizations of biologically active proteins from the venom of this species. Methods: The various proteins in the crude venom were fractionated and analyzed by a combination of chromatographic separations and proteomic analysis techniques such as gel filtration, RP-HPLC, 1D electrophoresis, in-gel digestion, tandem mass spectrometry and protein database search. The pharmacological properties of Naja haje legionis venom were assessed using in vitro preparations using rodents and chicks. Results: Our venomic strategy allowed the identification of 64 proteins and peptides from known database which can classified into 17 families according to their biological activities. We were able to identify cobra venom factor, L-aminoacid oxidases, acetylcholinesterase, metalloproteinase, disintegrin, cysteine-rich secretory proteins, nerve growth factor, phospholipases A2, vespryns, kunitz-type inhibitor, short neurotoxins, long neurotoxins, weak neurotoxins, neurotoxin like proteins, muscarinic toxins, cytotoxins and cardiotoxins. Pharmacological tests showed that Naja haje legionis venom contained neurotoxic activities inducing irreversible blockage of neuromuscular transmission in both rodent and chick nerve-muscle preparations. This venom also exhibit myotoxic and cardiotoxic activities. Conclusions: These results showed the potency and the complexity of the various proteins present in the venom of Naja haje legionis,which present a very similar pattern to other cobra venoms. The contribution of the different components in venom toxicity deserves further investigations.